The Identity of Community Traditional Shophouse Along the Makong River, Nakhon Phanom Province - คงศักดิ์ตระกูล, สุธน (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
This article aimed to present the identity of community traditional shophouse along the Mekong River of Nakhon Phanom Province. The objectives of the article are to study the settlement and architectural identity of traditional shophouse along the Mekong River of Nakhon Phanom Province and to study the architectural pattern and the characteristic of buildings in order to use as database to set up some guidelines for single-storey shophouse conservation. The methods of the study are related literatures and theories reviewing, physical characteristics surveying and shophouse residents interviewing. The result of the study were found that first, In the past, traditional communities along the Mekong River were settle by commercial purpose and the initial style of those shophouse was influenced by Vernacular architecture and Chinese architecture and later western styles methods of construction was adopted. Second, the distinct identity of the shophouse was the adaptation of its utility space that could be changed in accordance with residential characteristic and external appearance. The shophouse was distinctly adjusted to be in line with social context and local culture. Third, the growth and the development of the city reduced roles of the traditional commercial community along the Mekong River and new communities were occurred along the expansion of roads. The style of the shophouse was changed to be more modern. The result of this study was presented as the development of settlement and the architectural identity of single-storey shophouse and also as the promotion of building conservation to further maintain architectural identity of the traditional community along the Mekong River of Nakhon Phanom Province.